Sustainability Analytics Framework for ESG Performance and Circular Economy in Indonesia's Electric Vehicle Industry - Ricardo Pakpahan; Ignatius Luddy Indra Purnama (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
The rapid growth of Indonesia’s electric vehicle (EV) industry highlights the urgency of integrating sustainability into business strategies. However, many companies still face challenges in translating Environmental, Social, and Governance (ESG) commitments into operational practices that can strengthen long-term competitiveness. This study aims to develop and test a Sustainability Analytics Framework that links ESG Performance, Circular Economy Practices, Sustainability Analytics, and Sustainable Competitiveness. Using a quantitative approach, data were collected from 225 respondents representing managers and staff in EV-related industries, including automotive, battery production, and nickel mining. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4.0. Results indicate that ESG Performance significantly influences both Circular Economy and Sustainability Analytics. Furthermore, Circular Economy and Sustainability Analytics serve as mediators that strengthen the effect of ESG on Sustainable Competitiveness. Among the tested relationships, Sustainability Analytics shows the strongest effect on competitiveness, emphasizing the role of data-driven decision-making in the global EV ecosystem. This study contributes by offering an integrated framework that guides Indonesian industries in meeting international sustainability standards such as the EU Battery Passport while enhancing long-term competitive advantage.